Correction to: Mandibular response after rapid maxillary expansion in class II growing patients: a pilot randomized controlled trial - Roberta Lione; Valerio Brunelli; Lorenzo Franchi; Chiara Pavoni; Bernardo Quiroga Souki; Paola Cozza (SpringerOpen, 2018)
In the publication of this article (1) there is an error in the Methods section.